Access and challenges to Use online learning materials in higher education students at remote areas of Nepal: A case study in Bajura - Pandit, Suresh Prasad (Journal of Jayaprithvi Multiple Campus, 2025)
The integration of online learning materials into higher education has the potential to enhance educational accessibility and flexibility. However, students in remote areas of Nepal, such as Bajura, face significant barriers in accessing and utilizing these resources. This study investigates the current state of internet infrastructure, digital access and the challenges faced by higher education students in Bajura. Utilizing a mixed research design, data was collected through questionnaire and semi-structured interviews involving 30 students and 10 educators from various disciplines. Findings indicate that internet connectivity is poor, with most students relying on mobile devices with moderate to poor service quality. Linguistic barriers, particularly the predominance of English-language materials, hinder effective learning. Socio-economic constraints, including the high cost of internet services, limited access to devices and gender based discrimination make further exacerbate the issue. Digital literacy levels are variable, with students showing considerable deficiencies in essential digital skills compared to educators, who generally exhibit better proficiency. The study underscores the need for improved digital infrastructure, more accessible educational resources in local languages, provide training to the students’ to use tools like Google Translate, DeepL, QuillBoot and other application for the translation of texts and enhanced digital literacy training for both students and educators to bridge the educational divide.